2012
DOI: 10.1136/archdischild-2012-302287
|View full text |Cite
|
Sign up to set email alerts
|

Successful public health action to reduce the incidence of symptomatic vitamin D deficiency

Abstract: A programme of universal rather than targeted Healthy Start vitamin D supplementation for pregnant and lactating women and young children has led to a substantial decrease in cases of symptomatic vitamin D deficiency in a high-risk population. Supplementation was also started at a younger age than in the national programme. This approach has implications for the delivery of vitamin D supplementation programmes in similar populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
54
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 7 publications
4
54
1
Order By: Relevance
“…Although there may be justified concerns over the low doses used in supplements, a recent study of universal supplementation reported considerable reduction in the incidence of symptomatic vitamin D deficiency in a child population. 21 As a result, NICE is considering the costeffectiveness of the Healthy Start vitamin programme becoming universal. 22 Vitamin D deficiency is an important public health issue.…”
Section: Discussionmentioning
confidence: 99%
“…Although there may be justified concerns over the low doses used in supplements, a recent study of universal supplementation reported considerable reduction in the incidence of symptomatic vitamin D deficiency in a child population. 21 As a result, NICE is considering the costeffectiveness of the Healthy Start vitamin programme becoming universal. 22 Vitamin D deficiency is an important public health issue.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, vitamin D deficiency rickets is a treatable disease, and targeting preventative strategies at high risk populations, in whom the incidence rates are up to 200 times that of white children [20] may be appropriate. Indeed the incidence of symptomatic VDD in children aged less than 5 years more than halved following the introduction of universal free vitamin D supplements for all pregnant women and children under 5 years in Birmingham, where 75% of the population are from high risk ethnic backgrounds [108].…”
Section: Discussionmentioning
confidence: 99%
“…There are two studies looking at the impact of universal supplementation in groups at risk of vitamin D deficiency in the UK [28,29]. Moy et al [29] described that vitamin D supplementation with 400 IU/day led to a 59% fall in the incidence rate of symptomatic vitamin D deficiency and almost universal public awareness of vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Moy et al [29] described that vitamin D supplementation with 400 IU/day led to a 59% fall in the incidence rate of symptomatic vitamin D deficiency and almost universal public awareness of vitamin D deficiency. Similarly, successful routine vitamin D supplementation was reported in refugees in Sydney, Australia [30].…”
Section: Discussionmentioning
confidence: 99%